LOYALITAS KARYAWAN DITINJAU DARI KUALITAS KEHIDUPAN KERJA DAN KEPUASAN KERJA KARYAWAN - , FAIVINA RAHMAWATI FAJRIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Human resources have a very important role in the achievement of company objectives. Therefore, a company should pay attention to the employeesâ quality of work life as well as the employeesâ job satisfaction. The employees who feel satisfied with a company will provide big loyalty and contribution in order that the company objectives will be achieved. The research was to test the role of job life quality and the employeesâ job satisfaction toward the employeesâ loyalty, so that the employees would be able to stay in a quite long period of time. The sample of the research was 121 employees (N = 121) in PT. MAK with minimum 3 years of tenure. The data gathering method in the research was a quantitative one by means of questionnaire distribution and the questionnaire included the quality of work life, the job satisfaction and the employee loyalty with five-scale answers in the form of likert scale through the two-predictor multiple analysis method. The findings of the research support the hypothesis that altogether the quality of work life and the job satisfaction might predict the employee loyalty (R=0.372